2018
DOI: 10.1177/1350508418779649
|View full text |Cite
|
Sign up to set email alerts
|

Organizing in the Anthropocene

Abstract: The functioning of the biosphere and the Earth as a whole is being radically disrupted due to human activities, evident in climate change, toxic pollution and mass species extinction. Financialization and exponential growth in production, consumption and population now threaten our planet's life-support systems. These profound changes have led Earth System scientists to argue we have now entered a new geological epoch -the Anthropocene. In this introductory article to the Special Issue, we first set out the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
8

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 85 publications
1
67
0
8
Order By: Relevance
“…biodiversity loss and global climate change), it has been suggested that earth has transitioned from Holocene (meaning "wholly recent") to a new geological epoch: the Anthropocene (meaning "humanly recent"see Corlett, 2015;Lewis and Maslin, 2015;Malhi, 2017;Ruddiman, 2013;Steffen et al, 2011;Waters et al, 2016), where human action is a driver of global environmental change (Rockström et al, 2009, p. 472). Regardless of whether this proposition is sustained in a strict geological sense (see Section 2), the idea of the Anthropocene is motivating and informing debates in many disciplines, including those linked to researching organizations (Ergene et al, 2018;Heikkurinen et al, 2016;Hoffman and Jennings, 2015;Jennings and Hoffman, forthcoming;Whiteman et al, 2013;Wright et al, 2018). Building off this literature, the paper proceeds in three parts.…”
Section: Introductionmentioning
confidence: 99%
“…biodiversity loss and global climate change), it has been suggested that earth has transitioned from Holocene (meaning "wholly recent") to a new geological epoch: the Anthropocene (meaning "humanly recent"see Corlett, 2015;Lewis and Maslin, 2015;Malhi, 2017;Ruddiman, 2013;Steffen et al, 2011;Waters et al, 2016), where human action is a driver of global environmental change (Rockström et al, 2009, p. 472). Regardless of whether this proposition is sustained in a strict geological sense (see Section 2), the idea of the Anthropocene is motivating and informing debates in many disciplines, including those linked to researching organizations (Ergene et al, 2018;Heikkurinen et al, 2016;Hoffman and Jennings, 2015;Jennings and Hoffman, forthcoming;Whiteman et al, 2013;Wright et al, 2018). Building off this literature, the paper proceeds in three parts.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, all life forms have intrinsic value and right to exist [46]. For post-Anthropocene politics, this entails judgment and self-limitation [106], as humans do not have the right to reduce or destroy the diversity of other life forms with other reasons than fulfilling their primary needs and desires [107]. Based on this premise, the human organization should always be put in relation to other beings and ecosystems [11].…”
Section: Agency Intrinsicality and The Right For Existencementioning
confidence: 99%
“…It also offers significant trans-and interdisciplinary research opportunities for scholars interested in the interactions between governance, management and social studies. In the wake also of broader debates about the role of business and capitalism contributing to societal progress and the Anthropocene (Malm and Hornborg, 2014;Pichler et al, 2017;Wright et al, 2018)…”
Section: Integrating Global Goals Into New Business Modelsmentioning
confidence: 99%
“…Yet while much attention has focused on society and policy makers (e.g., Bai et al, 2016;Folke et al, 2016;Patterson et al, 2017), we know significantly less about how businesses exercise agency as part of ESG (Bouteligier 2011;Lim et al, 2018) and specifically how they contribute to the UN SDGs (Kolk et al, 2017). Concerns are mounting over how large corporations are being governed (Mayer, 2016;Mayer et al, 2017) and how businesses generally should operate in the Anthropocene (Albareda and Waddock 2018; Dyck and Greidanus 2016; Hoffman andJennings 2015, 2018;Whiteman et al, 2013;Whiteman and Yumashev, 2018;Wright et al, 2018). As finance, economics and management underlie much of human social activities, the role of business and corporate actors in achieving the SDGs needs to be examined (Shrivastava et al, 2019).…”
mentioning
confidence: 99%